Acidic and enzymetic extraction of pectin from peels of soursop, passion fruit and dragon fruit - Liew, Shan Qin (2015)
Pectin has been intensively used as natural gelling agent and stabilizer to alter the rheological properties of food ingredients in most food processing industries today in order to achieve desired textural quality. Three tropical fruit peels, the yellow passion fruit, red dragon fruit, and soursop were selected for optimising the pectin extraction using citric acid by varying pH from 2.0 to 4.5 and extraction time from 30 to 120 minutes at 70 ⁰C. The extracted pectin was measured in term of pectin yield and the degree of esterification (DE). Peel of yellow passion fruit gave the highest pectin yield of 14.60% and DE of 67.31%, followed by the red dragon fruit with pectin yield of 13.04% and DE of 57.81% and lastly the soursop with 5.87% and 47.65% respectively. The optimised pectin yield and DE obtained from the response surface methodology using the central composite design were within 13.40 ± 0.8% and 51.71 ± 3.83% at extraction pH of 2.37 and extraction time of about 61 ± 3 minutes for both the yellow passion fruit and dragon fruit. The pH of extraction solvent had more significant effect on pectin yield (p< 0.05) with high pectin yield produced at pH 2.0. With high amount of pectin and DE obtained from the yellow passion fruit peels, further pectin extraction method using enzyme was studied as to compare with the acidic extraction method. The celluclast® 1.5L enzyme was used and concentration was varied from 0.49-2.84% (w/w). The extraction temperature studied was from 35 to 85 ⁰C and extraction time was from 30 to 120 minutes. The extracted pectin yield and DE were compared with those extracted using citric acid concentration from 0.05-0.21% (w/w). The enzymatic extraction gave higher pectin yield of 9.17% with DE of 86.96% compared to acidic extraction at 7.71% with 78.57% respectively. The acidic and enzymatic extraction methods of pectin from yellow passion fruit peels gave similar optimised yields of about 7.14 ± 0.02%. However, optimised DE of the enzymatic extraction method was higher at 85.45% compared to the acidic extraction method at 71.02%. The optimised enzyme concentration was 1.67% (w/w) at 102 minutes at 61.11 ⁰C. Pectin yield was most significantly affected by extraction time (p<0.05) while DE was most affected by enzyme concentration (p<0.05). Similarly, for acidic extraction, citric acid concentration had most significant effect on DE (p<0.05) while temperature had more significant effect on pectin yield (p<0.05). The optimised citric acid concentration was 0.19% (w/w) at 75°C for 102 minutes. Morphology of pectin obtained using the scanning electron microscopy (SEM) suggested that the wet passion fruit pectin obtained from the acid extraction gave a smooth, compact and little wrinkle structure while the enzymatic extraction was with more wrinkle. The pectin obtained from acidic and enzymatic extraction respectively to test for it’s ability to form gel by adding water (control), calcium chloride, sugar. Combination of water, sugar and calcium gave the highest pectin gel viscosity with sugar giving much influence on the viscosity of pectin gel. The pectin gels exhibited shear thinning or pseudoplastic behaviour with n<1.